Neurosteroid Activation of GABA-A Receptors: A Potential Treatment Target for Symptoms in Primary Biliary Cholangitis? - Aaron Wetten; Laura Ogle; George Mells; Vinod S. Hegade; Laura Jopson; Margaret Corrigan; Jeremy Palmer; Maja Johansson; Torbjörn Bäckström; Magnus Doverskog; David E. J. Jones; Jessica K. Dyson (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. A third of patients with primary biliary cholangitis (PBC) experience poorly understood cognitive symptoms, with a significant impact on quality of life (QOL), and no effective medical treatment. Allopregnanolone, a neurosteroid, is a positive allosteric modulator of gamma-aminobutyricacid-A (GABA-A) receptors, associated with disordered mood, cognition, and memory. This study explored associations between allopregnanolone and a disease-specific QOL scoring system (PBC-40) in PBC patients. Method. Serum allopregnanolone levels were measured in 120 phenotyped PBC patients and 40 age and gender-matched healthy controls. PBC subjects completed the PBC-40 at recruitment. Serum allopregnanolone levels were compared across PBC-40 domains for those with none/mild symptoms versus severe symptoms. Results. There were no overall differences in allopregnanolone levels between healthy controls (median = 0.03 ng/ml (IQR = 0.025)) and PBC patients (0.031 (0.42), p=0.42). Within the PBC cohort, higher allopregnanolone levels were observed in younger patients (r (120) = −0.53, p<0.001) but not healthy controls (r (39) = −0.21, p=0.21). Allopregnanolone levels were elevated in the PBC-40 domains, cognition (u = 1034, p=0.02), emotional (u = 1374, p=0.004), and itch (u = 795, p=0.03). Severe cognitive symptoms associated with a younger age: severe (50 (12)) vs. none (60 (13); u = 423 p=0.001). Conclusion. Elevated serum allopregnanolone is associated with severe cognitive, emotional, and itch symptoms in PBC, in keeping with its known action on GABA-A receptors. Existing novel compounds targeting allopregnanolone could offer new therapies in severely symptomatic PBC, satisfying a significant unmet need.